Factors that affecting work life balance among teachers in Johor Bahru - Sheikh Mohd Effendy, Siti Helwa (2018)
In the need for excellence is year 2020, the government of Malaysia have been assign on the new regulation on education system that may affect the teachers and educators. Despite of the changing in technology and modernization throughout the year, teacher’s work life balance might be affected. Teacher stress is defined as experiences in teachers of unpleasant, negative emotions like anger in resulting from some aspect of their work as teachers (Kyriacou, 2001). The teaching professions are the most high risk for stress compare to other profession (Chan and Hui, 1995; Pithers and Forgaty, 1995). The Health and Safety Executive in the United Kingdom reported that teaching was the most stressful occupation, compared to other occupations. It was also reported that two out of five teachers in the United Kingdom experienced stress, compared to one in five workers from other occupations. Meanwhile in Malaysia , a study conducted on teachers has revealed that 4.4% of the 48,258 respondents or about 2,000 teachers, experience moderate stress. The aim of the study is to explore the factors that affecting work life balance among teachers and how to overcome the problems in Johor Bahru. There were four independent variables in the study that included workload, role conflict, job satisfaction and work attitude. Meanwhile, work life balance is the dependent variable. Based on the findings form the results, it was showed that two variables that have significant impact on the work life balance among teachers which is job satisfaction and work attitude. The remaining independent have no relationship on the work life balance. We can see that teachers have problem with their job satisfaction and work attitude.